Improvement in Visual Function in Patients with Inherited Diseases of the Retina Following Acupuncture Treatment - Blechschmidt, T.; Krumsiek, M.; Todorova, M. G. (Klinische Monatsblätter für Augenheilkunde, 2016)
Background: The aim of this pilot study was to examine the short-term effect on visual function of acupuncture treatment in a cohort of patients with inherited diseases of the retina. Patients and Methods: A prospective pilot study was performed on 14 patients (10 ♀, 4 ♂; mean age: 43.43 y (± 19.72 y)), with the clinically and electrophysiologically confirmed diagnosis of inherited disease of the retina. Acupuncture treatment consisted of needle application to the body and ears and was performed following a standardized protocol. The treatment was scheduled for 10 half-hour sessions over five weeks. Visual function was measured before acupuncture, between acupuncture treatments and after the end of treatment. Objective measurements included best corrected visual acuity (ETDRS charts), contrast vision (CSV-1000, Vector Vision) and Goldmann perimetry (isopters 3IIIe; Haag-Streit). Subjective evaluation was based on evaluation questionnaires. To exclude the effect of variability on the psychophysical tests, a non-acupuncture control group (Nr: 8; 5 ♀, 3 ♂; mean age: 38.56 y (± 9.08 y)) was taken for comparison. Results: All patients with inherited diseases of the retina showed general improvement in objective visual functions, with post-/pre- acupuncture improvement in: visual acuity (p = 0.031, left eyes), contrast vision (p = 0.015 and p = 0.041; both eyes) and widening of the temporal radius of the visual field (0.013; left eyes). Subjectively, all patients reported better daytime, color and contrast vision, better visual focus and less visual tiredness. In addition, some general symptoms, such as longer sleep-onset time, feeling cold, and migraine/headache attacks were significantly reduced. Conclusions: The acupuncture protocol improved visual function in our patients with inherited diseases of the retina and was well tolerated. Nevertheless, the long-term effect of this complementary therapy remains to be evaluated.
Keywords: acupuncture; contrast vision; Flammer syndrome; inherited retinal diseases; visual function; perimetry